Corporate Governance: Implications for Environmental, Social, and Governance (ESG) Performance - Khornida, Dewi; Sitorus, Winda Fionita; Yuwono, Wisnu (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2025)
This research was conducted to examine the impact of board diversity on the ESG (environmental, social, and governance) performance of companies. The study investigates board diversity in terms of board attributes such as board size, board gender diversity, and board independence. The data used is secondary data obtained from financial and sustainability reports of manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sample of this research consists of 29 companies, with a total of 145 data points. The sampling method used to obtain data is purposive sampling based on certain criteria. The analysis method used is panel regression, and STATA software is employed for data processing. The results of the study indicate that board gender diversity and board size do not affect ESG performance. However, board independence does have an impact on ESG performance.